2016
DOI: 10.1007/s11661-016-3453-3
|View full text |Cite
|
Sign up to set email alerts
|

Correlation Between Microstructures and Tensile Properties of Strain-Based API X60 Pipeline Steels

Abstract: The correlation between the microstructures and tensile properties of strain-based American Petroleum Institute (API) X60 pipeline steels was investigated. Eight types of strain-based API X60 pipeline steels were fabricated by varying the chemical compositions, such as C, Ni, Cr, and Mo, and the finish cooling temperatures, such as single-phase and dual-phase regions. In the 4N and 5C steels, the volume fractions of bainitic ferrite (BF) and the secondary phases increased with the increasing C and adding Cr in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…The yield strength and tensile strength of the cT 570 and cT 630 steels meet the aPi requirements for X70 (485 MPa minimum yield strength and 570 MPa minimum tensile strength) in all directions. The cT 570 and cT 630 steels in all directions show discontinuous yielding behavior because PF is the dominant microstructure in both steels [20][21][22]. The tensile test data for the CT 630 specimen indicate higher yield strength and tensile strength than the cT 570 specimen at both 0° and 90°.…”
Section: Resultsmentioning
confidence: 92%
“…The yield strength and tensile strength of the cT 570 and cT 630 steels meet the aPi requirements for X70 (485 MPa minimum yield strength and 570 MPa minimum tensile strength) in all directions. The cT 570 and cT 630 steels in all directions show discontinuous yielding behavior because PF is the dominant microstructure in both steels [20][21][22]. The tensile test data for the CT 630 specimen indicate higher yield strength and tensile strength than the cT 570 specimen at both 0° and 90°.…”
Section: Resultsmentioning
confidence: 92%
“…Furthermore, the uE increases significantly with the increase in E j from 15 to 75 kJ/cm. The uE is closely related to slip of dislocation: once dislocations slip over long distances without encountering barriers, high uE is generated [50,51]. When the E j = 15 and 35 kJ/cm, there are many DTs and ferrite lath boundaries in the microstructure, and the dislocation density is high (Figure 4a,b and Figure 7e,f).…”
Section: Effect Of E J On Cghaz Tensile Propertiesmentioning
confidence: 98%
“…it has been reported that an increase in the strength level deteriorates the hydrogen embrittlement resistance [10,11]. However, it is challenging to understand the effect of each microstructural constituent on the hydrogen embrittlement resistance of pipeline steels owing to their very complicated microstructures [12][13][14][15][16]. Thus, it is necessary to investigate the correlation between characterized microstructural constituents and the hydrogen embrittlement resistance to develop aPi pipeline steels possessing an excellent combination of strength and hydrogen embrittlement resistance.…”
Section: Introductionmentioning
confidence: 99%